Key factors limiting carbon nanotube strength: Structural characterization and mechanical properties of multi-walled carbon nanotubes - Keiichi SHIRASU (The Japan Society of Mechanical Engineers, 2017)
In this study, the nominal tensile strength, Young's modulus and Weibull scale and shape parameter of the nominal tensile strength distribution of the MWCNTs synthesized by a thermal chemical vapor deposition (CVD) method were investigated by conducting uniaxial tensile tests. In addition, the structural defects which induced the failure of the MWCNTs were observed by a transmission electron microscope (TEM). TEM observations revealed that the MWCNTs exhibited several types of structural defects: discontinuous flaws such as holes, kinks and bends and remnant catalysts even though crystalline graphene layers were aligned with the MWCNT axis. The nanotube tested in this study fractured at the structural defects such as discontinuous flaws and kinks and bends, suggesting that the tensile strength of the CVD-grown MWCNTs used in this study was dominated by the above-mentioned structural defects. The tensile-loading experiments demonstrated that the nominal tensile strength, Young's modulus and Weibull scale and shape parameter of the as-grown MWCNTs were 5.2 ± 2.1 GPa, 210 ± 150 GPa, 5.9 GPa and 2.7, respectively. The MWCNTs used in this study showed larger Weibull scale parameter values compared with both the CVD-grown and arc-discharge-grown MWCNTs evaluated an earlier study. This suggested that there was an optimal nanotube structure for increasing nominal tensile strength; not too weak but also not too strong inter-tube coupling to permit an adequate load transfer between the nanotube walls and thus a consequent clean break fracture. We also investigated the effects of the thermal annealing on the mechanical properties of the MWCNTs. The structural changes observed after annealing led to no significant impact on the nominal tensile strength of the MWCNTs, which was mainly due to incomplete removal of the structural defects by thermal annealing.